135 Closing the audit loop: the hidden symptoms in multiple sclerosis. Issue 3 (9th February 2012) - Housden, M; Desai, M; Davis, E
Abstract : Patients with Multiple Sclerosis (MS) have a variety of symptoms "making it difficult for healthcare professionals to detect all relevant changes."(1) NICE recommends that "service professionals in regular contact with people with MS, should consider in a systematic way whether a 'hidden' problem is contributing to their clinical situation."(1) To tackle this challenge an audit was conducted following which an assessment tool was developed. This annual checklist is now used to ensure all symptoms are discussed. (2) The following audit closes the loop and examines whether symptom identification in MS clinics improved. Forty patient notes from a 1-year period were randomly selected from MS clinics and reviewed. The annual checklist was easily identifiable. The original audit proforma was used to check symptoms addressed in clinic. 47.5% of annual checklists were completed. Symptom identification had improved: Continence issues: 85% for bladder (previously 76%); 80% for bowel (72%): 55% memory (28%): 25% emotional disturbances (2%); 60% fatigue (22%); 65% mood (48%); 72.5% muscle weakness (36%); 77.5% spasms (96%); 60% skin sensations (16%); 65% speech and swallow (36%); 17.5% sexual relationships (6%); 82.5% pain (62%); 60% pressure sores (42%); 52.5% tremor and balance and 47.5% vision. Following the introduction of the annual checklist, improvements were made to symptom identification. Health professionals remained poor at addressing problems with sex and relationships in MS patients.